2015
DOI: 10.1002/etc.3041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ecological risks from environmental releases of decamethylcyclopentasiloxane (D5)

Abstract: Decamethylcyclopentasiloxane (D5) is used in personal care products and industrial applications. The authors summarize the risks to the environment from D5 based on multiple lines of evidence and conclude that it presents negligible risk. Laboratory and field studies show that D5 is not toxic to aquatic organisms or benthic invertebrates up to its solubility limit in water or porewater or its sorptive capacity in sediment. Comparison of lipid-normalized internal concentrations with measured concentrations in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…Because D5's maximum fugacity (i.e., its vapor pressure) is 22.7 Pa at 25 °C, it is theoretically possible for D5 to cause nonpolar narcosis. However, nonpolar narcosis has not been observed or demonstrated in toxicity tests . Nonpolar narcosis is also unlikely to occur in the environment, because calculated activities and corresponding fugacities in biota are several orders of magnitude below values corresponding with nonpolar narcosis (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because D5's maximum fugacity (i.e., its vapor pressure) is 22.7 Pa at 25 °C, it is theoretically possible for D5 to cause nonpolar narcosis. However, nonpolar narcosis has not been observed or demonstrated in toxicity tests . Nonpolar narcosis is also unlikely to occur in the environment, because calculated activities and corresponding fugacities in biota are several orders of magnitude below values corresponding with nonpolar narcosis (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…Available toxicity data for D5 have been compiled, reviewed, and discussed in Fairbrother et al . That study shows that there are no reported concentrations associated with observed toxic effects of D5 in any medium.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this review is to compile and review empirical studies of the bioaccumulation behavior of D5 with the aim of providing information that is useful in the categorization of D5 for bioaccumulation. Similar efforts addressing persistence, toxicity, and risk of D5 are discussed in accompanying studies in the present issue of Environmental Toxicology and Chemistry .…”
Section: Introductionmentioning
confidence: 86%
“…38 For this reason, toxicity observed at concentrations in excess of the maximum sorptive capacity might have been due to "neat" cVMS. The maximum sorptive capacity of organic carbon (OC) may be calculated for a material as the product of the compound's water solubility (mg L −1 ) and its K OC value (L kg −1 OC).…”
Section: Bioconcentration and Toxicitymentioning
confidence: 99%